2012
DOI: 10.1007/s00464-012-2558-z
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic relevance of gastric cancer staging by endoscopic ultrasound

Abstract: EUS identifies the low risk subgroup (uUICC stage I or uT1/2) with similar performance as pUICC stage I or stage pT1/2 in gastric cancer and very similar survival characteristics. EUS thus may be the noninvasive method of choice for preoperative selection of patients for immediate resection versus neoadjuvant chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 17 publications
0
13
0
3
Order By: Relevance
“…These results indicated that gastric cancers that were detected using US were at a more advanced stage compared with those that were not detectable using US. The advancement of gastric cancer is represented with T staging (23), which can be evaluated using transabdominal US with patients drinking water prior to the scan, or using endoscopic US (24,25). In the current study, it was difficult to evaluate pT staging using US as the patients did not consume water prior to screening, and thus pT staging was evaluated subsequent to surgical resection.…”
Section: Discussionmentioning
confidence: 92%
“…These results indicated that gastric cancers that were detected using US were at a more advanced stage compared with those that were not detectable using US. The advancement of gastric cancer is represented with T staging (23), which can be evaluated using transabdominal US with patients drinking water prior to the scan, or using endoscopic US (24,25). In the current study, it was difficult to evaluate pT staging using US as the patients did not consume water prior to screening, and thus pT staging was evaluated subsequent to surgical resection.…”
Section: Discussionmentioning
confidence: 92%
“…With regards to predicting survival, contrasting data have been reported. Jurgensen et al reported preoperative EUS T staging and pathologic T staging equally predicted survival while more recently, Spolverato et al, concluded that survival in patients with advanced preoperative EUS T staging was significantly overestimated when compared to surgical pathologic staging .…”
Section: Discussionmentioning
confidence: 99%
“…With regards to predicting survival, contrasting data have been reported. Jurgensen that survival in patients with advanced preoperative EUS T staging was significantly overestimated when compared to surgical pathologic staging [20,21]. Multi-detector row CT imaging is an additional modality for determining preoperative TNM staging.…”
Section: Discussionmentioning
confidence: 99%
“…Zusammenfassend sollte der EUS komplementär zur CT für die Selektion von Patienten für eine perioperative Therapie eingesetzt werden. Ungeachtet der eingeschränkten EUS-Genauigkeit insbesondere für die Differenzierung zwischen T2-und T3-Tumoren und beim Lymphknotenstaging erlaubt die endosonografische Stratifizierung in Risikogruppen (Serosainfiltration, Aszitesnachweis, Lymphknotenbefall) zwischen Patienten mit einer relativ günstigen Prognose (hohe Wahrscheinlichkeit einer R0-Resektion und günstige 5-Jahres-Prognose) und Patienten mit ungünstiger Prognose (eingeschränkte Wahrscheinlichkeit einer R0-Resektion und ungünstige 5-Jahres-Prognose) zu diskriminieren [306,307,[318][319][320]342]. Die Auswertung der prospektiven Daten eines US-amerikanischen tertiären onkologischen Zentrums zeigte eine Genauigkeit der Risikostratifizierung durch EUS von 73 %.…”
Section: Leber Und Mediastinale Lymphknotenunclassified